The eschatological expectation of Isaiah 40-66 with special reference to Israel and the nations - Odendaal, Dirk H. (Phillipsberg, NJ Presbyterian and Reformed, 1970)
Includes bibliographical references.
Keywords: Bible. O.T. Isaiah. Apocalyptic passages -- criticism, interpretation, etc